PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN INNOVATION CAPABILITY TERHADAP CUSTOMER SATISFACTION PADA PERBANKAN SYARIAH MILIK PEMERINTAH DI KOTA PEKANBARU - Diana Sri Dewi; Sri Restuti (Jurnal Ekonomi, 2014)
The research aimed to know the effect of each dimension of Customer Relationship Management either directly or through Innovation Capability to Customer Satisfaction. The data collection using questionnaire that has been done a pretest with 165 respondents selected by using purposive sampling method. The main analysis is structural equetion modeling using Partial Least Square (PLS) as a variance/component based approach which does not required the fullfillment o data. The result of the research show that how good the prediction model of Customer relationship Management for Innovation Capability. But only Long-term Partnership and Technology-based CRM dimensions that have a great positive significant influence, with Long-term Partnership are most important, while Information Sharing tending to moderate significant influence lowering Innovation Capability. The improvement Information Sharing could change the effect to be positive. The facts also indicated how good the prediction model of Customer Relationships Management and Innovation Capability for Customer Satisfaction. Innovation Capability give the significant positive effect among medium and large as Long-term Partnership dimensions. While Technology-based CRM with a great direct influence.In this case, Innovation Capability plays an important role to produced the great total effect as moderating from Long-term Partnerships and Technology-based CRM. Customer Involvement indicated as initial point inCcustomer Relationship Management strategy and together with Joint Problem Solving role to strengthen Long-term Partnership.